An evaluation of the recruitment and selection policies and practices of the National Health Insurance Authority. A case study of the Brong-Ahafo Region. - Asafo-Adjei, Birago (2015)
A thesis submitted to the Department of Human Resource and Organizational Development, KwameNkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of MASTER OF BUSINESS ADMINISTRATION (HRM OPTION).